Progress in Analytical Methods for the Characterization, Quality and Safety of the Beehive Products - Sanna, Gavino; Ciulu, Marco; Picò, Yolanda; Spano, Nadia; Tuberoso, Carlo I.G (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint presents some recent results from applying original analytical methods to the most renowned hive matrices. Particular consideration was given to methods devoted to the attribution of the origin of honey and propolis, but also studies dealing with the chemical characterization of honey and other hive matrices are here reported. Attention has also been paid to the use of optimized methods of elemental analysis in several hive products for quality and safety purposes, but also for environmental biomonitoring. The treatment of the data was often achieved through multivariate analysis methods, which made it possible to obtain reliable classifications of honeys and propolis according to their botanic or geographical origin.